Soybean adaption to high‐latitude regions is associated with natural variations of GmFT2b, an ortholog of FLOWERING LOCUS T. (25th January 2020) - Chen, Li; Cai, Yupeng; Qu, Mengnan; Wang, Liwei; Sun, Hongbo; Jiang, Bingjun; Wu, Tingting; Liu, Luping; Sun, Shi; Wu, Cunxiang; Yao, Weiwei; Yuan, Shan; et al.
ABSTRACT: Day length has an important influence on flowering and growth habit in many plant species. In crops such as soybean, photoperiod sensitivity determines the geographical range over which a given cultivar can grow and flower. The soybean genome contains ~10 genes homologous to FT, a central regulator of flowering from Arabidopsis thaliana . However, the precise roles of these soybean FTs are not clearly. Here we show that one such gene, GmFT2b, promotes flowering under long‐days (LDs). Overexpression of GmFT2b upregulates expression of flowering‐related genes which are important in regulating flowering time. We propose a 'weight' model for soybean flowering under short‐day (SD) and LD conditions. Furthermore, we examine GmFT2b sequences in 195 soybean cultivars, as well as flowering phenotypes, geographical distributions and maturity groups. We found that Hap3, a major GmFT2b haplotype, is associated with significantly earlier flowering at higher latitudes. We anticipate our assay to provide important resources for the genetic improvement of soybean, including new germplasm for soybean breeding, and also increase our understanding of functional diversity in the soybean FT gene family. Abstract : In an effort to understand the molecular genetic basis of flowering time in soybean, we have isolated and characterized GmFT2b, a soybean FT gene homolog. We used overexpression and CRISPR/Cas9‐induced targeted gene mutations to show that GmFT2b regulates flowering in soybean, but only under long days. We also sequenced this gene from 195 soybean cultivars in different maturity groups (MGs). Our analysis showed that one GmFT2b haplotype, Hap3, is found only in early‐maturing cultivars in MGs 0–2, and correlates with their ability to flower in environments located at high latitudes in northeastern China.